INVESTIGAÇÃO PSICOPEDAGÓGICA NO ENSINO SUPERIOR: EXPERIÊNCIAS NO PARFOR/UFPI - Maria da Silva, Elizabete; Maria de Sousa Leal, Francisca; Maria Leal, Josileide; Maria Araujo Luz, Luciana; Elizete Leal Borges, Maria; Regina da Silva, Marlene; Lucia Lima Leite Mendes, Débora (Revista Form@re - Parfor/UFPI, 2026)
.